PENGARUH TINGKAT SUKU BUNGA, BOND RATING, UKURAN PERUSAHAAN, DEBT TO EQUITY RATIO (DER) TERHADAP YIELD TO MATURITY OBLIGASI KORPORASI DI BEI PERIODE TAHUN 2010-2012 - Hendaryadi; Meina Wulansari Yusniar; Abdul Hadi (Universitas Lambung Mangkurat, 2018)
This study aimed to analyze the effects of interest rates, bond rating, company size, and debt to equity ratio (DER) of the yield to maturity (YTM) of corporate bonds in Indonesia Stock Exchange. Previous researches showed different results, therefore, it is necessary to re- study by testing the four variables on the yield to maturity. The population in this study was all corporate bonds listed and traded on the Stock Exchange in the period of 2010-2012. There were 324 bonds. Based on the Purposive sampling criteria, 66 bonds were obtained. The research hypothesis was tested by multiple linear regression (multiple regression) and the analysis tools were company's financial statements, market price of the bond, SBI interest rate and bond ratings. The results showed that the variable interest rates and the debt to equity ratio did not significantly affect the yield to maturity of the bonds. Variable bond rating and company size gave significant negative effects ontheyield tomaturity of the bonds